In vitro cytotoxic and apoptotic activity of polysaccharide rich Morinda citrofolia fruit on MCF-7 cells - Srinivasahan, Vennila; Durairaj, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Morinda citrofolia fruit or noni is well-known traditional medicine that has both antioxidant and anticancer activity. This study was designed to investigate experimentally the anti-apoptotic effect of polysaccharide isolated from M. citrofolia fruit against MCF-7 breast cancer cells. Treatment of the MCF-7 cells with varied concentrations (1.0, 0.5, 0.25, 0.125, 0.062.5, and 0.03125 mg/ml) of polysaccharide isolated from M. citrofolia fruit resulted in dose-dependent cytotoxicity marked primarily by loss of cell viability in 3-(4,5-dimethyl thiazol-2-yl)-5-diphenyl tetrazolium bromide assay, and internucleosomal DNA fragmentation in DNA ladder assay. Furthermore, M. citrofolia fruit mediated cytotoxicity was found to be associated with transactivation of caspase 3 and p53, and down regulation of Bcl-2. From the result, it was proved that polysaccharide fractions of M. citrofolia fruit extract exhibited significant anti-proliferative and apoptotic activity thereby showing valuable application in developing anticancer drug products. Keywords: MCF-7 cells, p53, Bcl-2, Caspase-3, Morinda citrofolia and polysaccharide. Â 